WAYS TO FORM GOOD WRITING SKILLS OF ELEMENTARY SCHOOL STUDENTS ON THE BASIS OF A NOTEBOOK (IN THE EXAMPLE OF THE FIRST GRADE) - Khudjayeva Rano Ruzimuradovna (Galaxy International Interdisciplinary Research Journal, 2023)
In the realm of elementary education, the development of writing skills lays a crucial foundation for a student’s academic journey. As educators, parents, and guardians, it is imperative to adopt effective strategies that not only foster a love for writing but also instill essential skills from an early age. This article explores the significance of utilizing notebooks as a tool to enhance the writing abilities of first-grade students, emphasizing creative and structured approaches to encourage meaningful engagement.